How did the scientific publication system respond to the Covid-19 pandemic? - Renan Moritz Varnier de , Almeida (Iberoamerican Journal of Science Measurement and Communication, 2022)
The Covid-19 pandemic introduced new complicating factors for the process of scientific publication, such as an unprecedented volume of article submissions. These changes have the potential to significantly alter how scientific communication is done, thus demanding scrutiny. To assess how the scientific publication system responded to the challenges brought by the Covid-19 pandemic. The following topics of interest were analyzed with the help of a review of the pertinent scientific literature: a) How were review quality and publication speed affected by the increased volume of Covid-19-related submissions; b) How were Covid-19 retraction and citation rates affected; and c) How was the scientific communication process impacted by the widespread use of “preprints” as a valid (“citable”) source of information. Concerning review quality, some extremely dubious articles on Covid-19 treatment managed to be published, some of which were in relatively prestigious journals. Regarding retractions (contrary to initial reports), no increase in retractions rate was evident as time passed and the system reached its “steady state”. As for preprints, problems associated with their use are the practice of “retracting” (withdrawing) preprints with no adequate retraction standards and how to evaluate preprint quality effectively. As a whole, the scientific publication system seems to have survived the unusual circumstances arising from the pandemic; e.g., no increase in retractions rates was observed. Problems remain to be dealt with, particularly regarding improving the peer review quality and the citation/evaluation/retracting of preprints.